Adverse event profile differences between pralsetinib and selpercatinib: a real-world study based on the FDA adverse events reporting system - Jie, Qiong; Li, Yuanyuan; Jing, Li; Chen, Jinjin; Li, Yang (Frontiers in Pharmacology, 2024)
Aims: The objective of this study is to compare the adverse events (AEs) associated with pralsetinib and selpercatinib. Methods: To evaluate the imbalance of AEs linked to pralsetinib and selpercatinib in real-world data, the reporting odds ratio (ROR) was utilized to detect potential signals of AEs. Stratified analysis was conducted to examine the differences in AEs occurring among different genders and age groups taking pralsetinib and selpercatinib. Results: FAERS received 891 reports for pralsetinib and 569 reports for selpercatinib. Our analysis confirmed expected AEs like hypertension, fatigue, and elevated transaminase levels. Unexpected AEs such as rhabdomyolysis, myocardial injury and cognitive disorder were associated with pralsetinib, while selpercatinib was linked with pulmonary embolism, deep vein thrombosis, and pericardial effusion. The risk of AEs such as decreased platelet count, anemia, decreased white blood cell count, pneumonitis, asthenia, and edema caused by pralsetinib is significantly higher than that of selpercatinib. In contrast, the risk of AEs such as ascites, elevated alanine aminotransferase, and elevated aspartate aminotransferase caused by selpercatinib is significantly higher than that of pralsetinib. Women treated with pralsetinib experience higher rates of hypertension, pulmonary embolism, and blurred vision than men, who are more susceptible to rhabdomyolysis. Adults between 18 and 65 years are more likely to experience taste disorder, edema, and pulmonary embolism than individuals older than 65, who are particularly vulnerable to hypertension. For patients treated with selpercatinib, males demonstrate a significantly higher incidence of QT prolongation, urinary tract infection, and dysphagia. Individuals aged 18 to 65 are more likely to experience pyrexia and pleural effusion than those older than 65, who are more prone to hypersensitivity. Conclusions: In the clinical administration of pralsetinib and selpercatinib, it is crucial to monitor the effects of gender and age on AEs and to be vigilant for unlisted AEs.